Efficacy of Topical Treatment for Acute Rhinosinusitis in Children - Takhsinovna , Nasretdinova Makhzuna; qizi , Khusanova Dilnoza Abdukhamid; Alisherovich , Normuradov Nodir (American Journal of Biomedicine and Pharmacy, 2025)
The article is devoted to the problem of acute rhinosinusitis in children. The data of separate researches on estimation of efficiency and expediency of using hypertonic solutions of sea water in complex treatment of rhinosinusitis are presented. It is shown that inclusion of a spray with hypertonic solution of sea water in the treatment scheme allows to improve objective indicators of nasal function and patient’s condition in a short period of time, shortens the total duration of the disease, reduces the risk of complications.